Simple Extraction of Cannabinoids from Female Inflorescences of Hemp (Cannabis sativa L.) - Milena Szalata; Mariola Dreger; Aleksandra Zielińska; Joanna Banach; Marlena Szalata; Karolina Wielgus (Molecules, 2022)
The high interest in non-psychoactive cannabidiol increases the need for efficient and straightforward cannabidiol (CBD) extraction methods. The research aimed to compare simple methods of cannabinoid extraction that do not require advanced laboratory equipment. This work assesses the content of total CBD and Δ9-tetrahydrocannabinol (Δ9-THC) in popular solvents such as water and ethanol extracts. Hemp raw material was analyzed with Gas Chromatography with a Flame Ionization Detector (GC-FID), while extracts were tested by High-Performance Liquid Chromatography (HPLC). The female inflorescences of three varieties of industrial hemp were tested: Futura 75, KC Dora, and Tygra (different sowing and N fertilization densities). Tygra (T/10/30) showed the highest content of CBD (0.064%) in water extracts. However, in 80% tincture from Futura 75 (F/30/30), a higher CBD content of 1.393% was observed. The use of 96% ethanol for extraction and ultrasound enabled the highest CBD content to be obtained: 2.682% in Futura 75 (F/30/30). Cold water extraction showed no effect on Δ9-THC content, while hot water extraction increased content from 0.001% in KC Dora to 0.002% in Futura 75 (F/30/30) and Tygra, but the changes were statistically insignificant. Application of 80% ethanol revealed the significantly highest content of Δ9-THC in KC Dora, from 0.026% (K/30/90) to 0.057% (K/30/30), as well as in Tygra (T/30/30) (0.036%) and Futura 75 (F/30/30) (0.048%). The use of ethanol extraction in combination with ultrasound could be an efficient method of obtaining cannabinoids.